Nonsecular resonances for the coupling between nuclear spins in solids - Kropf, Chahan; Fine, Boris V. (Physical review. B, Condensed matter and materials physics, 2012)
Spin-spin relaxation in solid-state nuclear-magnetic resonance in strong magnetic fields is normally described only with the help of the secular part of the full spin-spin interaction Hamiltonian. This approximation is associated with the averaging of the spin-spin interaction over the fast motion of spins under the combined action of the static and the radio-frequency (rf) fields. Here, we report a set of conditions (nonsecular resonances) when the averaging over the above fast motion preserves some of the nonsecular terms entering the full interaction Hamiltonian. These conditions relate the value of the static magnetic field with the frequency and the amplitude of the rf field. When the above conditions are satisfied, the effective spin-spin interaction Hamiltonian has an unconventional form with tunable parameters. This tunable Hamiltonian offers interesting possibilities to manipulate nuclear spins in solids and can shed new light on the fundamental properties of the nuclear-spin-spin relaxation phenomenon.
Gesehen am 26.07.2018